Urinary Exosome-Derived microRNAs Reflecting the Changes in Renal Function in Cats - Ichii, Osamu; Ohta, Hiroshi; Horino, Taro; Nakamura, Teppei; Hosotani, Marina; Mizoguchi, Tatsuya; Morishita, Keitaro; Nakamura, Kensuke; Sasaki, Noboru; Takiguchi, Mitsuyoshi; Sato, Ryo; Oyamada, Kazuhisa; et al. (Frontiers in Veterinary Science, 2018)
Increased incidence of kidney disease (KD) is a common concern in human and companion animals. Cats, in particular, are highly susceptible to KD. Novel KD biomarkers would help to address these problems. Therefore, we are focusing on microRNA, a highly conserved nucleic acid, as a KD biomarker for various animals. We previously reported that altered levels of urinary exosome (UExo)-derived microRNAs indicate renal pathologies in dogs. This study comprehensively examined UExo-derived microRNAs, which reflected the KD status in cats. The examined cats were divided into two groups: normal renal function (NR) and KD. Based on our previous data in dogs and cats, as well as the present data on UExo-derived microRNAs in cats by next-generation sequencing, let-7b, let-7f, miR-10a, miR-10b, miR-21a, miR-22, miR-26a, miR-27b, miR-146a, miR-181a, miR-191, and miR-486a were identified as biomarker candidates. In summary, the levels of UExo-derived let-7b, miR-22, and miR-26a significantly decreased in cats with KD from the early stages of the disease. UExo-derived miRNA levels normalized to urinary creatinine or total RNA of miR-21a was significantly higher in the KD group. Importantly, the ratio of UExo-derived miR-21a to let-7b showed a significant and strongest correlation with serum creatinine (ρ = 0.751), blood urea nitrogen (ρ = 0.754), and urinary creatinine (ρ = -0.421) among all examined indices. Further, the ratio of miR-181a to let-7b or miR-10b significantly correlated with the progression of renal dysfunction in the KD group. Thus, we identified that UExo-derived microRNAs in cats, and their raw and normalized levels could indicate altered renal function.